Seismic Response to Injection Well Stimulation in a High‐Temperature, High‐Permeability Reservoir. (20th June 2019) - Hopp, Chet; Sewell, Steven; Mroczek, Stefan; Savage, Martha; Townend, John
Abstract: Fluid injection into the Earth's crust can induce seismic events that cause damage to local infrastructure but also offer valuable insight into seismogenesis. The factors that influence the magnitude, location, and number of induced events remain poorly understood but include injection flow rate and pressure as well as reservoir temperature and permeability. The relationship between injection parameters and injection‐induced seismicity in high‐temperature, high‐permeability reservoirs has not been extensively studied. Here we focus on the Ngatamariki geothermal field in the central Taupō Volcanic Zone, New Zealand, where three stimulation/injection tests have occurred since 2012. We present a catalog of seismicity from 2012 to 2015 created using a matched‐filter detection technique. We analyze the stress state in the reservoir during the injection tests from first motion‐derived focal mechanisms, yielding an average direction of maximum horizontal compressive stress ( S Hmax ) consistent with the regional NE‐SW trend. However, there is significant variation in the direction of maximum compressive stress ( σ 1 ), which may reflect geological differences between wells. We use the ratio of injection flow rate to overpressure, referred to as injectivity index, as a proxy for near‐well permeability and compare changes in injectivity index to spatiotemporal characteristics of seismicity accompanying each test. Observed increases in injectivity index are generally poorly correlated with seismicity, suggesting that the locations of microearthquakes are not coincident with the zone of stimulation (i.e., increased permeability). Our findings augment a growing body of work suggesting that aseismic opening or slip, rather than seismic shear, is the active process driving well stimulation in many environments. Plain Language Summary: When industries inject fluid into the Earth, oftentimes earthquakes are the result. Although this presents a hazard to nearby infrastructure and populations, studying these events helps us understand how fluid is moving underground and the processes that create earthquakes. In this paper, we describe over 9, 000 earthquakes that occurred over a 4‐year period at a geothermal field on the North Island of New Zealand. The details of where and when they occurred and how big they were give us clues about fractures ∼3, 000‐m underground and therefore how easily fluid can move from point A to point B underground. We focus on two wells where operators injected cold water (∼20 °C) at high pressure to try to open fractures in the reservoir. This would allow them to extract and reinject more fluid and therefore produce more power. We found that, while some of these operations triggered earthquakes, the amount of fluid that could be pumped into the ground was not related to the number of earthquakes. This means that, in the future, companies may be able to design injection operations so that they achieve their goal of opening fractures underground, without also generating large earthquakes. Key Points: Seismicity is induced during borehole drilling and stimulation at the Ngatamariki geothermal reservoir The rate of seismicity and injectivity increase is decoupled during injection well stimulation Stress inversions from earthquake focal mechanisms reveal distinct stress states across the reservoir